CHALLENGES OF DIGITIZATION OF FINANCIAL TRANSACTIONS - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The products and services of different DeFi platforms are constantly being developed and can become part of open decentralized finance, i.e. function as a single financial platform. Open finance would enable standardization of data exchange and interoperability of different DeFi systems. The fact is, however, that decentralized finance arose as independent systems that are not part of a common conceptualization. The concept of open finance is also being developed within the traditional financial sector. The term open finance refers to the future open financial system, as a continuation of the development initiated by open banking, with the aim of making financial resources of clients more accessible in a wider range of services and platforms. A key condition for the development of open finance is user trust and "the creation of a wider single data market" (European Union, 2022: 5). The planned concept of open finance includes: a wider choice for customers through access to a more customized and personalized range of services and products; improving access to and use of financial services in all business segments; in line with data protection rules, providing consumers and businesses with greater transparency about how their data is used; facilitating data interoperability in open finance; embedding an open finance approach to client-centred services in a general cross-sectoral framework (European Union, 2022: 6).
Keywords: digitalization; financial transactions; challenges; technological innovation; virtual currencies